REKONSILIASI DALAM AL-QURAN - Muhammad Patri Arifin (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2015)
Islam as a thought explain alla aspects of life, both aspects of divinity and humanity aspects that make reconciliation as one of the solutions to face the world`s cucial conditions as result of hostilities and war. Reconcilition in the vacubalary of the Qur`an called islah or peace, which has the important objectives to maintain a relationship, not just among muslim in particular, but for people in general. So in this case, reconciliation can be categorized in several ways, namely reconciliation in temrs of faith or belief and worship, social, moral, also in terms of politics and government law. In the implementation, reconcilitation involves several parties, the parties to the dispute and the mediator in charge of mediating the dispute. Mediator required to act fairly and with dignity an also have sufficient scientific reputation. Disputants are also required to conduct an honest deliberation, do not insult or slander also full awareness and conduct of peace moreover instill on ourselves not to repeat acts tah may lead disunity. It is to realize the concept of brotherhood, harmony maintaining trust and caring between people and to realize the things that are far from disputes and violence, as we as to maintain social balance not only in religious life, but also in the state and nation.